Prion protein NMR structure and species barrier for prion diseases - Billeter, Martin (The National Academy of Sciences of the USA, 1997)
The structural basis of species specificity of transmissible spongiform encephalopathies, such as bovine spongiform encephalopathy or “mad cow disease” and Creutzfeldt–Jakob disease in humans, has been investigated using the refined NMR structure of the C-terminal domain of the mouse prion protein with residues 121–231. A database search for mammalian prion proteins yielded 23 different sequences for the fragment 124–226, which display a high degree of sequence identity and show relevant amino acid substitutions in only 18 of the 103 positions. Except for a unique isolated negative surface charge in the bovine protein, the amino acid differences are clustered in three distinct regions of the three-dimensional structure of the cellular form of the prion protein. Two of these regions represent potential species-dependent surface recognition sites for protein–protein interactions, which have independently been implicated from in vitro and in vivo studies of prion protein transformation. The third region consists of a cluster of interior hydrophobic side chains that may affect prion protein transformation at later stages, after initial conformational changes in the cellular protein.